Կենսաէմուլգատորների և L-կարնիտինի օգտագործման արդյունավետության որոշումը բրոյլերների ցածր կալորիականությամբ կերաբաժիններում - Վարդանյան, Հ. Ռ․ (ՀԱԱՀ հիմնադրամ)
Մսային ուղղության թռչունների կերի ինքնարժեքի նվազեցման և մթերատվության բարձրացման նպատակով ՌՈՍՍ-308 կրոսի բրոյլերների՝ սահմանված նորմայից ցածր կալորիականությամբ կերաբաժիններում հավելվել են կենսաէմուլգատոր և L-կարնիտին: Ըստ հետազոտությունների արդյունքների՝ բարելավվել են բրոյլերների մթերատվությունը, կերի կոնվերսիան, մսային հատկությունները և մսի որակը, նվազել է մսի ինքնարժեքը։ Ուստի նշված հավելումները մսային ուղղության թռչունների կերաբաժիններում կարող են կիրառվել որպես թռչնամսի արտադրության շահութաբերության բարձրացման արդյունավետ և անվնաս միջոց: С целью снижения себестоимости кормов и повышения продуктивности мясных пород птиц в рацион бройлеров кросса ROSS 308 с калорийностью ниже установленной нормы были добавлены биоэмульгаторы и L-карнитин. Согласно результатам исследований, улучшились продуктивность бройлеров, конверсия корма, свойства и качество мяса, снизилась его себестоимость. Следовательно, указанные добавки могут быть использованы в рационе мясных пород птиц как эффективное и безопасное средство для повышения рентабельности производства птичьего мяса. During the research aimed at reducing the cost price of poultry feed and increasing their productivity lysofort bio-emulator and L-carnitine supplement were used. 4 groups of ROSS-308 broilers were made (100 heads each). The control group received feed portion corresponding to the nutrition value of ROSS-308 cross boiler feed, containing defined content of exchange energy (in the initial phase-3050 kcal/kg, in the growth period-3100 kcal/kg, and in the final stage-3200 kcal/kg). In the experimental groups, the efficiency of the exchange energy was artificially reduced, mostly due to low content of vegetable oil. Feed conversion, head maintenance, live broiler chickens of different ages, growth dynamics, average daily weight growth, meat qualities of slaughtered poultry were studied in all groups. According to the research results, compared with the control group, the indicators of feed conversion and average daily weight growth of broiler chicken fed by portions containing bio-emulator and L-carnitine were improved, which testifies to the increase in the availability of energy. Due to the synergy of joint application of bio-emulators and L-carnitine, feed conversion is improved, production costs and cost price are reduced, the productivity of broilers is increased, as well as the profitability of poultry production (not at the cost of increasing the consumer prices) and meat quality is improved (as a result of increasing the amount of protein and reducing fat). As an efficient and safe means to increase the profitability of poultry production, the bio-emulators and L-carnitine can be used in the feed of meat poultry.
Keywords: Անասնաբուժական բժշկագիտություն և անասնաբուծություն